Does Brand Image Certainly Mediate Relationships between e-WOM and Purchase Intention? A Case Study of Samsung Smartphone Marketing in Papua - W., Ivana; ., Uturestantix (Advances in Social Sciences Research Journal, 2018)
The purpose of this study is to investigate the effect and also interrelationship between the variables of e-WOM, brand image, and purchase intention of Samsung smartphones in Jayapura. 100 students from various colleges that spread across Jayapura city were sampled in this research. A quantitative approach with deduction and causal hypothesis testing was employed in this project. Cross-sectional method was also conducted in this study to design the survey with research time dimension. Sampling process of respondents were done using non-probability sampling with purposive sampling technique, by judgment sampling. To analyse data and test the hypotheses, multiple regression and hierarchical regression analyses were applied utilising statistical software, SPSSVer.21.0. The results of its hypothesis testing prove that e-WOM has a significant positive effect on brand image and purchase intention, while the brand image itself promotes a positive influence on purchase intention. Meanwhile the mediation testing demonstrates the brand image partially facilitates the relationship between e-WOM and purchase intention.